Drawings : The Pluralist Decade. - De Ak, Edit; Fox, Howard N.; Kardon, Janet; Krauss, Rosalind E.; Lorber, Richard; Neff, John Hallmark; Perreault, John; Museum of Contemporary Art, Chicago (Philadelphia : Institute of Contemporary Art, University of Pennsylvania, 1980)
Acconci, Vito ; Africano, Nicholas ; Anderson, Laurie ; Armajani, Siah ; Artschwager, Richard ; Attie, Dotty ; Aycock, Alice ; Bartlett, Jennifer ; Benglis, Lynda ; Borofsky, Jonathan ; Brown, Trisha ; Childs, Lucinda ; Christo ; Davis, Brad ; Dean, Laura ; Denes, Agnes ; Downey, Juan ; Eisenman, Peter ; Ferrara, Jackie ; Ferrer, Rafael ; Fleischner, Richard ; de Forest, Roy ; Girouard, Tina ; Glass, Philip ; Graves, Michael ; Graves, Nancy ; Grooms, Red ; Hejduk, John ; Hurson, Michael ; Hutchinson, Peter ; Ireland, Patrick ; Irwin, Robert ; Kozloff, Joyce ; Kushner, Robert ; Lanigan-Schmidt, Thomas ; LeWitt, Sol ; MacConnel, Kim ; Plimack Mangold, Sylvia ; Matta-Clark, Gordon ; Mayer Harrison, Helen ; Miss, Mary ; Morris, Robert ; Morton, Ree ; Oppenheim, Dennis ; Pfaff, Judy ; Pinto, Jody ; Pozzi, Lucio ; Reich, Steve ; Rockburne, Dorothea ; Rothenberg, Susan ; Samaras, Lucas ; Shields, Alan ; Singer, Michael ; Smithson, Robert ; Smyth, Ned ; Stella, Frank ; Tacha, Athena ; Trakas, George ; Le Va, Barry ; Wiley, William T. ; Wilson, Robert ; Zakanitch, Robert ; Zimmerman, Elyn ; Zucker, Joe
biografie
Drawings: The Pluralist Decade, Institute of Contemporary Art, University of Pennsylvania, Philadelphia, October 4, 1980 - November 9, 1980 ; Museum of Contemporary Art, Chicago, May 29, 1981 - June 26, 1981
Engels
boek